Private Self-consciousness, Self-reflection, Insight and Alcohol Consumption Among Young People and Adults - Leal,Cristyan Karla Nogueira (2019)
Abstract Private self-consciousness is a relevant metacognitive capacity in the self-regulation process, with possible implications in alcohol consumption. This research verified the influence of self-reflection and insight, dimensions of private self-consciousness, on drinking behavior. A total of 523 Brazilians, aged from 20 to 39 years old, participated in a survey by answering the Self-Reflection and Insight Scale and the AUDIT test. The results showed that women have higher levels of self-reflection, whereas men have higher levels of insight. With regard to alcohol consumption, young people drink at higher risk levels than adults. Self-reflection and insight were negatively correlated with alcohol consumption. Age and gender differences in the intensity of the correlation between variables and the influence of environmental factors on the regulation of drinking behavior are discussed.